Alcohol consumption and S-Klotho plasma levels in sedentary healthy middle-aged adults: A cross sectional study. (1st January 2019) - Jurado-Fasoli, Lucas; Amaro-Gahete, Francisco J.; De-la-O, Alejandro; Gutiérrez, Ángel; Castillo, Manuel J.
Highlights: Plasma S-Klotho, a longevity biomarker, is influenced by alcohol intake. Higher alcoholic drinks consumption is associated to lower plasma S-Klotho levels. The negative association is independent of body mass, lean mass or fat mass. Abstract: Introduction: Alcohol consumption is related to several diseases and injuries that accelerate the ageing process and increase the mortality and morbidity risk. The soluble form of the α-Klotho gene (called S-Klotho) is widely considered as a powerful anti-ageing biomarker. Aim: The aim of the present study was to analyze the association between alcohol consumption and S-Klotho plasma levels in sedentary middle-aged adults. Methods: 74 (39 women) middle-aged sedentary adults (40–65 years old) participated in the present study. Alcohol consumption was assessed with a food frequency questionnaire previously validated and with three non-consecutive 24-hours recall. The S-Klotho plasma levels were measured by ELISA using a soluble α-Klotho ELISA assay kit. Results: Total alcoholic drinks consumption was negatively associated with S-Klotho plasma levels (β=-17.031; R 2  = 0.096, P = 0.013). Furthermore, we observed that higher consumption of total alcoholic drinks is associated with lower S-Klotho plasma levels in middle-aged sedentary adults controlling for BMI (β=-16.372; R 2  = 0.201, P = 0.011), LMI (β=-31.854; R 2  = 0.305, P = 0.010) and for FMI β=-13.337; R 2  = 0.075, P = 0.049). Conclusion: In conclusion, our study shows that total alcoholic drinks consumption is negatively associated with the S-Klotho plasma levels in middle-aged sedentary adults.